Faktor-Faktor yang Ada Hubungan dengan Miopia pada Mahasiswa Fakultas Kedokteran di Beberapa Lokasi di Wilayah Indonesia Periode Tahaun 2008 sampai dengan Tahun 2019 - Alamsyah, Muhammad Asmawi; Madjid , Baedah; Launardo, Anastasia Vanny (Bosowa Medical Journal, 2023)
Myopia or nearsightedness is one of the refractive errors caused by light falling in front of the retina which has a high prevalence in the world and can interfere with academic activities, achievement, and productivity of a student's performance. Purpose to find out things that have a relationship with the occurrence of myopia in medical students in several locations in Indonesia in the period of the 2008 to the 2019. The research method is analytical research by synthesizing the results obtained by ten scientific research articles with a case control research design. Data from ten research journals analyzed showed a significant relationship between reading distance and myopia in medical students (p-value < 0.05%), while there was no significant relationship between family history of myopia, reading position, length of reading, lighting, and short distance activities with myopia (p value > 0.05%) in medical faculty students in several locations in Indonesia for the period 2008 to 2019. Myopia in medical students in several locations in Indonesia for the period 2008 to 2019 has a significant relationship with reading distance.